ANALISIS DETERMINAN FAKTOR KEPUTUSAN PEMBELIAN PADA PRODUK SCARLETT - Viki Kurnianti; Beta Asteria; Ruddy Trisantoso (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to analyze: 1) the effect of product quality on purchasing decisions for Scarlett products, 2) the influence of brand image on purchasing decisions for Scarlett products, 3) the effect of advertising on social media on purchasing decisions for Scarlett products. This study uses a quantitative approach with a survey method. The population in this study are consumers who have bought and used Scarlett products in Yogyakarta. The sampling technique used was non-probability sampling with purposive sampling technique or sampling based on certain characteristics. The sample in this study were 100 respondents. The data analysis method in this study used multiple linear regression analysis with SPSS 25 data processing program. The results showed that: 1) the product quality variable had a positive and significant effect on consumer decisions with a t count value of 2,226 greather than t table (1,984), 2) variable brand image has a positive and significant effect on consumer decisions with a t-count value of 4.423 greather than t table (1.984), 3) advertising variables on social media have a negative and insignificant effect on purchasing decisions with a t-count value of 0.704 less than t table (1.984 ). Based on the research results, the variables of product quality, brand image, and advertising on social media have an effect of 68.5% on purchasing decisions for Scarlett products in Yogyakarta and 31.5% of purchasing decisions are influenced by other variables.